PENGHAYATAN SERIKAT SOSIAL VINSENSIUS (SSV) AKAN SPIRITUALITAS SANTO VINSENSIUS A PAULO DI WILAYAH PAROKI SANTO CORNELIUS MADIUN - Stepanus Sakakaddut; Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Spirituality comes from the Latin word “spiritus” which means spirit, soul and spirit. God's spirituality and Spirit are one of the transcendent relationships that human beings intend to shape themselves according to God's ideals. Saint Vincent had an infinite awareness of the poor and set an example for the community who embraced it. The Society of Social Society Vincent is one of the communities that imitates the spirit of Saint Vincent's ministry. Society of Saint Vincent de Paul (SSV) is the international Christian community founded by Frederic Ozanam in Paris in 1833. The main concern of this community is to make the Church and the Catholic faith truly responsive to the conditions of society, especially the poor and neglected. This community has spread to Indonesia. SSV is now spread in various regions in Indonesia. The community area of Vincent Social Union referred to in this study is located in the parish of St Cornelius Madiun. The regional council of the SSV is located in the Parish of St Cornelius Madiun This study used qualitative research methods. Qualitative research method is a method of natural research in which researchers take data directly taken in the field. The study was conducted in March-April 2018 in the community of SSV. Research respondents in this scientific work are 8 (eight) people, 3 (three) administrators of the Regional Council, 1 (one) Spiritual Counselor, and 4 (four) Conference Organizer. The 8 (eight) respondents are still actively taking care of the SSV community to date. This scientific work was written with the purpose of knowinghow far the respondent lived the spirituality of Saint Vincent de Paulo in his ministry. The results show that most respondents understood the background of Saint Vincent, but the whole respondent did not know all the virtues of Saint Vincent. The respondents in this study knew the essence of the SSV, although there were still efforts to further develop this community among youth in particular.